A descriptive study of trauma patients transported by the KZN Helicopter Emergency Medical Services to the Durban Inkosi Albert Luthuli Central Hospital level one Trauma centre over a three - year period - Pule, Marwala Simon (Division of General Surgery, 2022)
Background KwaZulu-Natal (KZN), a large province of South Africa has vast distances to referral centres and time to definitive treatment is key in trauma care. Helicopter Emergency Medical Service (HEMS) is an invaluable prehospital asset for the transport of time sensitive trauma. This study reviews the impact of HEMS in the management of trauma at Inkosi Albert Luthuli hospital (IALCH) which is the only public accredited level one trauma centre in the province. Methods A retrospective descriptive study of polytrauma patients transported by HEMS in KZN to IALCH over a three-year period from 01 January 2014 to 01 January 2017. Data was collected around patient demographics, transfer details and patient outcomes. Results Over the three-year period, 117 HEMS transfers were reviewed, with the majority being male (90.6%). Just 26% of HEMS transfers were direct from the scene, with the balance being interhospital transfers largely from distant regional hospitals around the province. Some 60% of injuries were causes by vehicle crashes, and 31% by intentional injury. Mortality was 30% which is reflective of the high severity of injury of the cohort. The injury severity scores (ISS) (median 26 overall) of those who died was higher (median 38) (p-value= 0.0002), and there were more interventions before and during transfer such as thoracostomy, ventilation and immobilization. Some 88% were admitted to ICU at IALH. Conclusions: HEMS in the KwaZulu Natal province was mainly used for long-distance transfer of major trauma patients which is an appropriate use of this essential service, given the single major trauma centre in the province. The majority of patients that were transported by HEMS had severe injury, which was also associated with increased mortality outcomes. Rational use of this essential but expensive resource will require clear policy around the role of HEMS and call out criteria in each setting.